2018
DOI: 10.1108/9781787541993
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Power of Failure: Using Storytelling and Systems Engineering to Enhance Organizational Learning

Abstract: No part of this book may be reproduced, stored in a retrieval system, transmitted in any form or by any means electronic, mechanical, photocopying, recording or otherwise without either the prior written permission of the publisher or a licence permitting restricted copying issued in the UK by The Copyright Licensing Agency and in the USA by The Copyright Clearance Center. Any opinions expressed in the chapters are those of the authors. Whilst Emerald makes every effort to ensure the quality and accuracy of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In their research of failure, Newman and Wander (2018) found that a strikingly common denominator of many, if not most, program/project failures is less than adequate communication and a lack of defined roles and responsibilities. Wikis were instituted in part to resolve those risks and became the backbone and primary method of online communication and collaboration across the directorate.…”
Section: Wiki-enabled Teams Lessonsmentioning
confidence: 99%
“…In their research of failure, Newman and Wander (2018) found that a strikingly common denominator of many, if not most, program/project failures is less than adequate communication and a lack of defined roles and responsibilities. Wikis were instituted in part to resolve those risks and became the backbone and primary method of online communication and collaboration across the directorate.…”
Section: Wiki-enabled Teams Lessonsmentioning
confidence: 99%